Pengembangan LKPD Berbasis Project Based Learning untuk Meningkatkan Hasil Belajar pada Mata Pelajaran IPAS Kelas V - Valensi, Bunga; Rahmi, Ulfia; Zen, Zelhendri; Anugrah, Septriyan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to develop Student Worksheets (LKPD) based on Project Based Learning (PjBL) in improving learning outcomes in class V science subjects. The research method used is research and development using the 4D model. Research stages include define, design, development, and disseminate. The instruments used in this research were observation, interviews, documentation, and questionnaires. The validity test was carried out by 3 validators, namely 2 media validators and 1 material validator. Based on the results of the needs analysis, PjBL-based LKPD teaching materials are needed to improve student learning outcomes. The practicality test was carried out on 24 class V students of SD Negeri 14 Belanti Barat with the aim of finding out the practicality and effectiveness of the product. The results obtained by 2 media experts were 4.18 in the